JOB SATISFACTION AND EMPLOYEE MOTIVATION MEDIATES THE PRODUCTIVITY OF COVID-19 INDUCTED WORK FROM HOME (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
COVID-19 lockdown has tremendously effected and change the world in different aspects and dimensions. Working from home became inevitable after the Ghanaian government enforced a full lockdown in Accra, the capital, and Kumasi, the second largest city and this resulted too many workers beginning to work from home for the first time. Furthermore, reactions of employees varied in the midst of the pandemic as a result of many variables. The thrust of the study is to examine the mediating role of job satisfaction and motivation on productivity of working from home during the COVID-19 pandemic and its aftermath using Structural Equation Modelling. The researcher sampled 355 respondents in order to examine the mediating role. The findings however showed that job satisfaction and motivation mediate the relationship between organizational factors, employee engagement, and technical support on one hand, and productivity on the other hand. To reach higher levels of performance, the study recommends that practitioners establish techniques to foster good work attitudes and boost perceived organizational support.